Preparation method of sodium iron sulfate positive electrode material
Na12Fe6(SO4)9(PO4)2 type sodium ferrosulfate positive electrode material was prepared by mixing oxidized sodium ferrosulfate, sodium sulfate, phosphoric acid and ammonium bicarbonate with a carbon source, and then ball milling, spray drying and calcining, and sodium ferrosulfate was solved. The problems of poor ionic conductivity and low sodium deintercalation of the positive electrode material have achieved a high-performance sodium ion battery positive electrode material.
Patent Information
- Application Number
- CN202211519350.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-11-30
AI Technical Summary
The existing sodium ferrosulfate positive electrode materials have poor ionic conductivity, low sodium deintercalation amount and iron dissolution problems, which affect their electrochemical properties.
A mixture of chlorosodium ferrolum, sodium sulfate, phosphoric acid and ammonium bicarbonate and carbon source solution were ball milled, spray-dried and calcined at high temperature to prepare Na12Fe6(SO4)9(PO4)2 type sodium ferrosodium sulfate positive electrode material, which was doped by doping. The titanium and phosphate structures enhance ionic conductivity, and improve electron conductivity through carbon coating, control particle size and structure, and reduce iron dissolution.
The ionic conductivity and sodium ion removal amount of the sodium ion of the sodium ferric sulfate cathode material are significantly improved, the capacity and cycling performance of the battery are improved, and the dissolution of iron is reduced, and the stability and electrochemical performance of the material are improved.
Smart Images

Figure CN115863570B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a method for preparing a positive electrode material for a sodium ion battery, and in particular to a method for preparing a sodium iron sulfate positive electrode material. Background Art
[0002] Most of the existing sodium-ion battery cathode materials are transition metal oxides, and the oxide lattice has a large restriction on sodium ions, resulting in poor electrochemical performance. Sodium sulfate materials have attracted widespread attention due to their low price and easy synthesis and preparation process, and are a new generation of sodium-ion battery electrode materials with great potential.
[0003] Alluaudite type sodium ferrous sulfate positive electrode material has a high working voltage of 3.8V and can provide excellent energy density compared with other polyanion positive electrode materials. The crystal structure of sodium ferrous sulfate determines that there are inherent defects as a positive electrode material for sodium ion batteries, such as low electronic conductivity and poor rate performance. Carbon coating is considered to be one of the effective means to improve its electrical performance. However, carbon coating alone can only solve the problem of poor electronic conductivity, and the problem of poor ionic conductivity has not been solved. At the same time, there are certain problems with the deintercalation of sodium in sodium ferrous sulfate, because this material can only deintercalate half of the sodium ions, resulting in low capacity. How to deintercalate as many sodium ions as possible has become one of the keys to preparing this high-performance material. At the same time, the dissolution of iron is also an important indicator affecting the performance of sodium ferrous sulfate. How to avoid the dissolution of iron is also the key to preparing sodium ferrous sulfate materials.
[0004] Patent No. 201811030527.3 discloses a method for synthesizing a sodium iron sulfate positive electrode material, comprising the following steps: (1) weighing and mixing Na2SO4 and FeSO4·7H2O in a molar ratio of 1:(1.4-2.0), adding a carbon source to the mixture, wherein the mass of the carbon source is 0.75-1.5%wt of the mass of the mixture, and after mixing evenly, high-energy ball milling is performed for several times, each time for 20-30 minutes, to obtain a highly dispersed uniform powder; (2) calcining the uniform powder after ball milling at 320-380°C in an inert atmosphere of high-purity argon for 10-30 hours, cooling the product to room temperature with the furnace, and then manually grinding for 3-10 minutes until no large particles are visible to the naked eye, thereby obtaining the final material.
[0005] A sodium ion battery composite positive electrode material and a preparation method thereof disclosed in Patent No. 202111543146.7, the disclosed preparation method of sodium ferric sulfate includes: a1, vacuum drying ferrous sulfate heptahydrate to obtain anhydrous ferrous sulfate, the vacuum drying is carried out in a vacuum oven, and the vacuum drying temperature is 100-300°C; a2, sodium sulfate and ferrous sulfate are added to a zirconium oxide ball mill in proportion, zirconium oxide balls are added and nitrogen protection is injected, and ball milling is performed, A precursor is obtained; the ball-to-material ratio of the ball milling treatment is 50:1-1:20, the ball milling speed is 200-1000r / min, the rotational speed is 100-500r / min, and the ball milling time is 0.1-24h; a3, the precursor after ball milling is transferred to a box furnace, and heat-treated under a nitrogen protective atmosphere, and then the heat-treated product is crushed into powder to obtain sodium ferric sulfate, and the heat treatment temperature is 300-400°C, and the time is 0.1-24h.
[0006] The chemical reaction equation of sodium ferrocyanide is as follows: Na2Fe6(SO4)4(OH) 12 , which is mainly present in the iron removal slag of hydrometallurgy, with large particles, easy to filter, precipitate and wash. Its preparation method is simple and the preparation cost is low. Therefore, in Patent No. 201510077008.2, a process for preparing multi-element doped sodium ion battery electrode materials with yellow sodium iron alum is disclosed, and the disclosed content is: including adding sulfuric acid solution to yellow sodium iron alum, stirring until the yellow sodium iron alum is dissolved, evaporating the solution and pre-burning, mixing the obtained product with anhydrous sodium sulfate and a carbon forming agent, and then calcining to obtain the electrode material of the sodium ion battery. The present invention uses industrial waste slag to prepare high value-added electrode materials, which have the characteristics of low cost, good performance, simple process, etc., and has good economic and environmental benefits.
[0007] Therefore, it is necessary to further improve the existing technology. Summary of the invention
[0008] In order to solve the problems of poor ionic conductivity, sodium deintercalation and iron dissolution in the above-mentioned existing sodium ferric sulfate positive electrode materials, the present invention proposes a method for preparing a sodium ferric sulfate positive electrode material that can improve the ionic conductivity and the amount of sodium ions released from the product while reducing the amount of iron dissolution.
[0009] The present invention is achieved through the following technical solutions:
[0010] The preparation method of the above-mentioned sodium ferric sulfate positive electrode material is to add a mixture of yellow soda ash, sodium sulfate, phosphoric acid and ammonium bicarbonate to a carbon source solution, adjust the pH of the slurry to 1.8-2.5 with ammonium bicarbonate, and the molar ratio of the added yellow soda ash to sodium sulfate, phosphoric acid, ammonium bicarbonate and carbon source is 1:5.01-5.05:2.01-2.05:0.21-0.44. After stirring and mixing, the mixture is ground, dried and calcined to obtain the sodium ferric sulfate positive electrode material.
[0011] The method for preparing the sodium iron sulfate positive electrode material specifically comprises the following steps:
[0012] 1) Preparation of yellow sodium ferroaluminate:
[0013] Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, heated to 95-105°C under stirring, stirred at 200-300 r / min for 1-2 hours; then heated to 130-150°C for 1-2 hours, filtered and washed to obtain doped high-crystallinity sodium ferroaluminate;
[0014] 2) adding the obtained natrolite, sodium sulfate, phosphoric acid and ammonium bicarbonate mixture to the carbon source solution according to the molar ratio of natrolite to sodium sulfate, phosphoric acid and carbon source of 1:5.01-5.05:2.01-2.05:0.21-0.44, and adjusting the pH of the slurry to 1.8-2.5 with ammonium bicarbonate;
[0015] 3) After stirring and mixing the slurry in step 2), add it into a ball mill and grind it until the particle size of the slurry is 0.1-0.3 μm;
[0016] 4) spray drying, the particle size of the spray drying is 10-30 microns, and the moisture content is less than 0.5wt%;
[0017] 5) The spray-dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6(SO4)9(PO4)2.
[0018] The preparation method of the sodium iron sulfate positive electrode material, wherein: the calcined material is subjected to air flow pulverization to a material particle size of 1.5-2.5 μm, and then sieved, iron removed and vacuum packaged. The sieving uses an ultrasonic vibrating screen, passes through a 100-mesh screen, and iron removal uses an electromagnetic iron remover to remove iron until the magnetic foreign matter content is less than 1 ppm; vacuum packaging is carried out in a constant temperature and humidity room, with the humidity controlled within 10% and the temperature stabilized at 25±5°C.
[0019] The method for preparing the sodium ferric sulfate positive electrode material, wherein: in the step 1), the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.2-1.5:3:0.01-0.03:6.5-7, and the mass of the added pure water is 2-3 times the total mass of the sodium sulfate, ferric sulfate, titanyl sulfate and urea.
[0020] The method for preparing the sodium ferric sulfate positive electrode material, wherein: the carbon source is a mixture of glucose and pyridine, and the molar ratio of sodium ferroaluminate to sodium sulfate, phosphoric acid, glucose and pyridine is 1:5.01-5.05:2.01-2.05:0.2-0.4:0.01-0.04. The mass concentration of the carbon source solution is 1-2%.
[0021] The preparation method of the sodium iron sulfate positive electrode material, wherein: the calcination process, the heating rate is 1.5-2 ° C / h, then the insulation stage, the insulation temperature is 400-550 ° C, the insulation time is 6-9h, and then the temperature is reduced to ≤100 ° C, the cooling rate is 1-1.5 ° C / h. In the calcination process, the humidity in the furnace is controlled to ≤3%, and the calcination is carried out in a nitrogen atmosphere, and the oxygen content in the furnace is less than 5ppm.
[0022] Beneficial effects:
[0023] First, the present invention prepares titanium-doped sodium iron alum crystals, which have a relatively small primary particle size, a large BET, and high activity. The sodium iron alum is a crystal with low sodium and high iron. Then, sodium sulfate and phosphoric acid are added. Due to diffusion during the high-temperature calcination process, a structure with poor sodium and phosphate inside and rich sodium and phosphate outside is obtained. The advantages of this structure are: because the inside is doped with titanium, the ion conductivity is high, and the internal sodium ions can be effectively transmitted out. The internal structure after sodium removal is not easily corroded by the electrolyte because it is protected by the external phosphate-rich structure material. The phosphate introduced externally can realize anion doping and effectively protect sodium iron sulfate from being corroded by the electrolyte. At the same time, the introduction of phosphate can increase the amount of sodium ions released from the product, thereby increasing the capacity of the product.
[0024] At the same time, the present invention introduces carbon coating on the surface to control the primary particle size, and introduces a nitrogen-containing carbon source, thereby introducing nitrogen doping into the carbon network structure, greatly improving the conductivity of the carbon, thereby further improving the capacity of the product;
[0025] The present invention uses urea as a precipitant when preparing natrolite, which can avoid local over-concentration, thereby avoiding the generation of a large amount of iron hydroxide, thereby obtaining natrolite with a controllable sodium-iron molar ratio. However, conventional synthesis processes are prone to produce a large amount of iron hydroxide, so that the sodium-iron molar ratio of natrolite is uncontrollable;
[0026] The sodium ferric sulfate finally prepared by the present invention has high capacity, simple process, high product cycle performance and low iron dissolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a particle size distribution diagram of the sodium ferroaluminate prepared in Example 1 of the present invention;
[0028] Figure 2 This is a SEM image of the sodium ferroaluminate prepared in Example 1 of the present invention;
[0029] Figure 3 This is a SEM image of the sodium iron sulfate positive electrode material prepared in Example 1 of the present invention;
[0030] Figure 4 0.1C charge-discharge curve of the sodium iron sulfate positive electrode material prepared in Example 1 of the present invention;
[0031] Figure 5 This is a cyclic voltammetry test diagram of the sodium iron sulfate positive electrode material prepared in Example 1 of the present invention;
[0032] Figure 6 This is the 0.1C charge and discharge curve of the sodium iron sulfate positive electrode material prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The preparation method of the sodium ferric sulfate positive electrode material of the present invention comprises the following steps: adding a mixture of yellow sodium ferroaluminate, sodium sulfate, phosphoric acid and ammonium bicarbonate into a carbon source solution, stirring and mixing, adding the mixture into a ball mill for grinding, spray drying, and calcining to obtain the sodium ferric sulfate positive electrode material.
[0034] The specific steps include:
[0035] 1) Preparation of yellow sodium ferroaluminate:
[0036] Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, and then heated to 95-105°C under stirring, and reacted at this temperature at a stirring speed of 200-300 r / min for 1-2 hours; then heated to 130-150°C for 1-2 hours, and then filtered and washed to obtain doped high-crystallinity sodium ferroaluminate; the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.2-1.5:3:0.01-0.03:6.5-7, and the mass of pure water added is 2-3 times the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea;
[0037] After the reaction is finished, filtering, washing and drying are performed to obtain particles of yellow sodium ferroalloy;
[0038] The chemical reaction equation that occurs is as follows:
[0039] Na2SO4+3Fe2(SO4)3+6CO(NH2)2--Na2Fe6(SO4)4(OH) 12 +6CO2+6(NH4)2SO4
[0040] 2) adding the obtained yellow sodium ferroalite together with sodium sulfate and phosphoric acid to the carbon source solution and then adding ammonium bicarbonate, adjusting the pH of the slurry to 1.8-2.5 with ammonium bicarbonate, the molar ratio of the added yellow sodium ferroalite to sodium sulfate, phosphoric acid and carbon source is 1:5.01-5.05:2.01-2.05:0.21-0.44, and the mass concentration of the carbon source solution is 1-2%;
[0041] 3) After stirring and mixing the slurry in step 2), add it into a ball mill and grind it until the particle size of the slurry is 0.1-0.3 μm;
[0042] 4) spray drying, the particle size of the spray drying is 10-30 microns, and the moisture content is less than 0.5wt%;
[0043] 5) The spray-dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6(SO4)9(PO4)2, calcination process, heating rate is 1.5-2℃ / h, then insulation stage, insulation temperature is 400-550℃, insulation time is 6-9h, then cooling, cooling to material temperature ≤100℃, cooling rate is 1-1.5℃ / h; calcination process, control the humidity in the furnace ≤3%, calcination in nitrogen atmosphere, oxygen content in the furnace is less than 5ppm;
[0044] 6) The calcined material is subjected to air flow pulverization to a particle size of 1.5-2.5 μm, and then sieved, iron removed and vacuum packaged to obtain sodium iron sulfate positive electrode material.
[0045] Ultrasonic vibration screen is used for screening, and the product is screened through a 100-mesh screen. Electromagnetic iron remover is used for iron removal until the content of magnetic foreign matter is less than 1ppm. Vacuum packaging is carried out in a constant temperature and humidity room with humidity controlled within 10% and temperature stabilized at 25±5℃.
[0046] In step 1), the carbon source is preferably a mixture of glucose and pyridine, and the molar ratio of natantium ferroalloy to sodium sulfate, phosphoric acid, glucose and pyridine is 1:5.01-5.05:2.01-2.05:0.2-0.4:0.01-0.04.
[0047] The present invention is further described below with reference to specific embodiments.
[0048] Example 1
[0049] 1) Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, and then heated to 100°C under stirring, and reacted at a stirring speed of 200 r / min for 2 hours at this temperature, and then heated to 140°C for 1.5 hours, and then filtered and washed to obtain doped high-crystallinity sodium ferroaluminate;
[0050] The molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.35:3:0.02:6.8, and the mass of pure water added is 3 times the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea;
[0051] The purity of sodium sulfate is 99.7wt%, the calcium and magnesium content is less than 100ppm, and the other impurities are less than 50ppm;
[0052] The purity of ferrous sulfate is 99.2wt%, Fe 2+ The content of is less than 100ppm, the content of calcium and magnesium is less than 120ppm, the content of other impurities is less than 60ppm, and its pH is 1.3;
[0053] The water insoluble matter of urea is less than 150ppm. Then the urea is dissolved in water, and a cation exchange resin is added to adsorb the impurity cation ions before use.
[0054] The filter was filtered using a filter press, and then washed with pure water until the conductivity of the washing water was lower than 150 μS / cm;
[0055] Flash drying is used for drying to obtain granules of sodium ferroaluminate;
[0056] The chemical reaction equation that occurs is as follows:
[0057] Na2SO4+3Fe2(SO4)3+6CO(NH2)2--Na2Fe6(SO4)4(OH) 12 +6CO2+6(NH4)2SO4
[0058] The test data of the obtained yellow sodium ferroaluminate particles are shown in Table 1:
[0059] Table 1 Test data of yellow sodium ferroaluminate particles prepared in Example 1
[0060] index Na Fe S D10 data 4.97% 34.97% 13.11% 1.397μm ·D50 D90 BET Tap density Ca 3.918μm 10.598μm 21.5m2 / g 1.2g / mL 21.5ppm K Ni Cr Cu Ti 73ppm 0.4ppm 2.1ppm 0.1ppm 1689ppm
[0061] The particle size distribution diagram and SEM of the obtained yellow sodium ferroaluminate were measured. The results are as follows Figure 1 , Figure 2 From the test data of the product, the primary particle size is relatively small, about 100-200nm, and the BET is large and the activity is high.
[0062] 2) The obtained yellow sodium ferroalcite was added together with sodium sulfate and phosphoric acid to the carbon source solution, and then ammonium bicarbonate was added to adjust the pH of the slurry to 2.1. The carbon source was a mixture of glucose and pyridine. The molar ratio of the added yellow sodium ferroalcite to sodium sulfate, phosphoric acid and carbon source was 1:5.03:2.03:0.33, and the mass concentration of the carbon source solution was 1.8%.
[0063] 3) After stirring and mixing, add the mixture into a ball mill and grind until the particle size of the slurry is 0.18 μm.
[0064] 4) Spray drying is performed, and the particle size of the spray drying is 23 microns and the moisture content is less than 0.5wt%.
[0065] 5) The spray-dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6(SO4)9(PO4)2, calcination process, heating rate is 1.7℃ / h, then insulation stage, insulation temperature is 460℃, insulation time is 8h, then cooling, cooling to material temperature ≤100℃, cooling rate is 1.3℃ / h; calcination process, control the humidity in the furnace at 2.5%, calcination in nitrogen atmosphere, oxygen content in the furnace is 2.7ppm.
[0066] 6) The calcined material is subjected to air flow pulverization to a particle size of 1.56 μm, and then sieved, iron removed and vacuum packaged to obtain a sodium iron sulfate positive electrode material;
[0067] The screening is carried out by ultrasonic vibration screen, passing through a 100-mesh screen, and the iron removal is carried out by an electromagnetic iron remover to remove the magnetic foreign matter content to 0.37ppm. The vacuum packaging is carried out in a constant temperature and humidity room, with the humidity controlled within 10% and the temperature stabilized at 25±5℃.
[0068] The test data of the final product is shown in Table 2:
[0069] Table 2 Final product test data of Example 1
[0070]
[0071] The powder internal resistance test adopts the four-probe method and the test pressure is 15MPa.
[0072] The iron dissolution test method is: add 10g of material into 100mL of 0.1mol / L hydrochloric acid solution, soak for 30min at 35℃, then filter, measure the iron content of the filtrate, and the ratio of the total amount of iron in the solution to the mass of the product is the iron dissolution.
[0073] The compaction density was determined using a pressure of 3T.
[0074] D10 / D50 / D90 were measured by laser particle size analyzer, and water ultrasound was used for 60 seconds before measurement and then tested.
[0075] The electrical performance was measured using a soft pack test with a capacity of 1Ah. The positive electrode was made of this material, CNT and PVDF in a mass ratio of 0.9:0.03:0.07. It was sprayed onto a carbon-coated aluminum foil as the positive electrode. The negative electrode was a hard carbon material. The electrolyte was NaPF6-PC-EC-FEC, and the diaphragm was GF / C glass fiber. The temperature during normal temperature cycling was 25°C.
[0076] Product SEM Figure 3 As shown, from the scanning electron microscope, the primary particle size is about 70nm, and there are basically no single crystal particles with too large particle size. The largest single crystal particle does not exceed 500nm. The primary particle size is relatively small, and the primary particle distribution is relatively uniform.
[0077] Its 0.1C charge and discharge curve is as follows Figure 4 As shown, from the charge and discharge curves, the material performance of the present invention is relatively excellent, the polarization is small, and the coulomb efficiency is high.
[0078] Cyclic voltammetry test of the product Figure 5 As shown in the figure, the CV curve shows two pairs of redox peaks, corresponding to the Fe 2+ with Fe 3+ During the first charge, the two oxidation peaks were 3.75V and 4.15V, and the two reduction peaks were 3.15V and 3.65V. Because of the addition of titanium and phosphate, the redox peaks were still obvious at a scan rate of 1mV / s, and the polarization was reduced, which was beneficial to the migration of sodium ions.
[0079] Example 2
[0080] The preparation method of yellow sodium ferroaluminate of the present embodiment is as follows:
[0081] Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, and then heated to 95°C under stirring, and reacted at a stirring speed of 280r / min for 2h at this temperature, and then heated to 150°C for 1h, and then filtered and washed to obtain doped high-crystallinity sodium ferroaluminate; the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.5:3:0.03:7, and the mass of pure water added is 3 times the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea;
[0082] After the reaction is completed, filtering, washing and drying are performed to obtain particles of yellow sodium ferroaluminate;
[0083] The preparation method of the sodium ferric sulfate of the present embodiment is as follows:
[0084] A mixture of sodium ferrocyanide, sodium sulfate, phosphoric acid and ammonium bicarbonate is added to a carbon source solution, stirred and mixed, and then added to a ball mill for grinding, spray-dried, and calcined to obtain a sodium ferric sulfate positive electrode material;
[0085] The obtained yellow sodium ferroalite is added to the carbon source solution together with sodium sulfate and phosphoric acid, and then ammonium bicarbonate is added to adjust the pH of the slurry to 2.5. The carbon source is a mixture of glucose and pyridine. The molar ratio of the added yellow sodium ferroalite to sodium sulfate, phosphoric acid and carbon source is 1:5.01:2.01:0.24, and the mass concentration of the carbon source solution is 1.1%;
[0086] Then, after stirring and mixing, the mixture was added into a ball mill and ground until the particle size of the slurry was 0.3 μm;
[0087] Then it was spray dried, and the spray dried particle size was 30 microns and the moisture content was 0.46wt%;
[0088] The spray dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6(SO4)9(PO4)2, calcination process, heating rate is 1.5℃ / h, then insulation stage, insulation temperature is 400℃, insulation time is 9h, then cooling, cooling to material temperature ≤100℃, cooling rate is 1.5℃ / h; calcination process, control the humidity in the furnace ≤3%, use nitrogen atmosphere for calcination, oxygen content in the furnace is less than 5ppm.
[0089] The calcined material is pulverized by air flow to a particle size of 2.5 μm, and then sieved, iron removed and vacuum packaged to obtain sodium ferric sulfate material.
[0090] Ultrasonic vibration screen is used for screening, and the product is screened through a 100-mesh screen. Electromagnetic iron remover is used for iron removal, and the content of magnetic foreign matter is removed to 0.67ppm. Vacuum packaging is carried out in a constant temperature and humidity room, with humidity controlled within 10% and temperature stabilized at 25±5℃.
[0091] The test data of the final product is shown in Table 3:
[0092] Table 3 Final product test data of Example 2
[0093]
[0094] 0.1C charge and discharge curve Figure 6 As shown, judging from the charge and discharge curves, the electrical performance is excellent.
[0095] Example 3
[0096] The preparation method of yellow sodium ferroaluminate of the present embodiment is as follows:
[0097] Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, and then heated to 105°C under stirring, and reacted at this temperature at a stirring speed of 250r / min for 1.5h, and then heated to 130°C for 2h, and then filtered and washed to obtain doped high-crystallinity sodium ferroaluminate; the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.2:3:0.02:6.5, and the mass of pure water added is 2.5 times the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea;
[0098] After the reaction is completed, filtering, washing and drying are performed to obtain particles of yellow sodium ferroaluminate;
[0099] The preparation method of the sodium ferric sulfate of the present embodiment is as follows:
[0100] A mixture of sodium ferrocyanide, sodium sulfate, phosphoric acid and ammonium bicarbonate is added to a carbon source solution, stirred and mixed, and then added to a ball mill for grinding, spray-dried, and calcined to obtain a sodium ferric sulfate positive electrode material;
[0101] The obtained yellow sodium ferroalite is added together with sodium sulfate and phosphoric acid to a carbon source solution, and then ammonium bicarbonate is added to adjust the pH of the slurry to 2. The carbon source is a mixture of glucose and pyridine. The molar ratio of the added yellow sodium ferroalite to sodium sulfate, phosphoric acid, glucose and pyridine is 1:5.04:2.02:0.25:0.01, and the mass concentration of the carbon source solution is 1.5%;
[0102] Then, after stirring and mixing, the mixture was added into a ball mill and ground until the particle size of the slurry was 0.2 μm;
[0103] Then spray dried, the spray-dried particle size was 10 microns, the moisture content was 0.48wt%;
[0104] The spray dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6(SO4)9(PO4)2, calcination process, heating rate is 1.9℃ / h, then insulation stage, insulation temperature is 500℃, insulation time is 7h, then cooling, cooling to material temperature ≤100℃, cooling rate is 1.2℃ / h; calcination process, control the humidity in the furnace at 2.9%, calcination in nitrogen atmosphere, oxygen content in the furnace is 4ppm.
[0105] The calcined material is pulverized by air flow to a particle size of 2 μm, and then sieved, iron removed and vacuum packaged to obtain sodium ferric sulfate material.
[0106] Ultrasonic vibration screen is used for screening, and the product is screened through a 100-mesh screen. Electromagnetic iron remover is used for iron removal, and the content of magnetic foreign matter is removed to 0.67ppm. Vacuum packaging is carried out in a constant temperature and humidity room, with humidity controlled within 10% and temperature stabilized at 25±5℃.
[0107] The test data of the final product is shown in Table 4:
[0108] Table 4 Final product test data of Example 3
[0109]
[0110] Example 4
[0111] 1) Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, and then heated to 98°C under stirring, and reacted at this temperature at a stirring speed of 300r / min for 1h; then heated to 135°C for 2h, and then filtered and washed to obtain doped high-crystallinity sodium ferroaluminate; the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.4:3:0.01:6.9, and the mass of pure water added is 2.8 times the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea;
[0112] After the reaction is completed, filtering, washing and drying are performed to obtain particles of yellow sodium ferroaluminate;
[0113] The chemical reaction equation that occurs is as follows:
[0114] Na2SO4+3Fe2(SO4)3+6CO(NH2)2--Na2Fe6(SO4)4(OH) 12 +6CO2+6(NH4)2SO4
[0115] 2) adding the obtained yellow sodium ferroalite together with sodium sulfate and phosphoric acid to a carbon source solution, and then adding ammonium bicarbonate to adjust the pH of the slurry to 1.9, wherein the carbon source is a mixture of glucose and pyridine, the molar ratio of the added yellow sodium ferroalite to sodium sulfate, phosphoric acid, glucose and pyridine is 1:5.02:2.04:0.35:0.03, and the mass concentration of the carbon source solution is 2%;
[0116] 3) After stirring and mixing the slurry in step 2), add the mixture into a ball mill and grind until the particle size of the slurry is 0.1 μm;
[0117] 4) spray drying, the particle size of the spray drying is 20 microns, and the moisture content is 0.4wt%;
[0118] 5) The spray-dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12Fe6(SO4)9(PO4)2, calcination process, heating rate is 1.8℃ / h, then insulation stage, insulation temperature is 550℃, insulation time is 6h, then cooling, cooling to material temperature ≤100℃, cooling rate is 1℃ / h; calcination process, control the humidity in the furnace at 2.5%, calcination in nitrogen atmosphere, oxygen content in the furnace is 4.8ppm;
[0119] 6) The calcined material is subjected to air flow pulverization to a particle size of 1.5 μm, and then sieved, iron removed and vacuum packaged to obtain sodium iron sulfate positive electrode material.
[0120] The test data of the final product is shown in Table 5:
[0121] Table 5 Final product test data of Example 4
[0122]
[0123] Example 5
[0124] 1) Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, and then heated to 100°C under stirring, and reacted at this temperature at a stirring speed of 230r / min for 1.5h; then heated to 145°C for 1.5h, and then filtered and washed to obtain doped high-crystallinity sodium ferroaluminate; the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.3:3:0.02:6.7, and the mass of pure water added is twice the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea;
[0125] After the reaction is finished, filtering, washing and drying are performed to obtain particles of yellow sodium ferroalloy;
[0126] The chemical reaction equation that occurs is as follows:
[0127] Na2SO4+3Fe2(SO4)3+6CO(NH2)2--Na2Fe6(SO4)4(OH) 12 +6CO2+6(NH4)2SO4
[0128] 2) adding the obtained yellow sodium ferroalite together with sodium sulfate and phosphoric acid to a carbon source solution, and then adding ammonium bicarbonate to adjust the pH of the slurry to 1.8, the carbon source is a mixture of glucose and pyridine, the molar ratio of the added yellow sodium ferroalite to sodium sulfate, phosphoric acid, glucose and pyridine is 1:5.05:2.05:0.4:0.02, and the mass concentration of the carbon source solution is 1%;
[0129] 3) After stirring and mixing the slurry in step 2), add the mixture into a ball mill and grind until the particle size of the slurry is 0.25 μm;
[0130] 4) spray drying, the particle size of the spray drying is 18 microns, and the moisture content is 0.33wt%;
[0131] 5) The spray-dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6(SO4)9(PO4)2, calcination process, heating rate is 2℃ / h, then insulation stage, insulation temperature is 490℃, insulation time is 7h, then cooling, cooling to material temperature ≤100℃, cooling rate is 1.4℃ / h; calcination process, control the humidity in the furnace at 2.7%, calcination in nitrogen atmosphere, oxygen content in the furnace is 3.1ppm;
[0132] 6) The calcined material is subjected to air flow pulverization to a particle size of 1.8 μm, and then sieved, iron removed and vacuum packaged to obtain sodium iron sulfate positive electrode material.
[0133] The test data of the final product is shown in Table 6:
[0134] Table 6 Test data of final product of Example 5
[0135]
[0136] Example 6
[0137] 1) Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, and then heated to 105°C under stirring, and reacted at this temperature at a stirring speed of 230r / min for 1.5h; then heated to 150°C for 1.5h, and then filtered and washed to obtain doped high-crystallinity sodium ferroaluminate; the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.5:3:0.02:6.6, and the mass of pure water added is twice the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea;
[0138] After the reaction is completed, filtering, washing and drying are performed to obtain particles of yellow sodium ferroaluminate;
[0139] The chemical reaction equation that occurs is as follows:
[0140] Na2SO4+3Fe2(SO4)3+6CO(NH2)2--Na2Fe6(SO4)4(OH) 12 +6CO2+6(NH4)2SO4
[0141] 2) adding the obtained yellow sodium ferroalite together with sodium sulfate and phosphoric acid to a carbon source solution, and then adding ammonium bicarbonate to adjust the pH of the slurry to 1.8, the carbon source is a mixture of glucose and pyridine, the molar ratio of the added yellow sodium ferroalite to sodium sulfate, phosphoric acid, glucose and pyridine is 1:5.01:2.02:0.2:0.04, and the mass concentration of the carbon source solution is 1%;
[0142] 3) After stirring and mixing the slurry in step 2), add it into a ball mill and grind it until the particle size of the slurry is 0.3 μm;
[0143] 4) spray drying, the spray-dried particle size is 18 microns and the moisture content is 0.43wt%;
[0144] 5) The spray-dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6(SO4)9(PO4)2, calcination process, heating rate is 2℃ / h, then insulation stage, insulation temperature is 500℃, insulation time is 6h, then cooling, cooling to material temperature ≤100℃, cooling rate is 1.4℃ / h; calcination process, control the humidity in the furnace at 2.8%, calcination in nitrogen atmosphere, oxygen content in the furnace is 4.2ppm;
[0145] 6) The calcined material is subjected to air flow pulverization to a particle size of 1.8 μm, and then sieved, iron removed and vacuum packaged to obtain sodium iron sulfate positive electrode material.
[0146] The test data of the final product is shown in Table 7:
[0147] Table 7 Final product test data of Example 6
[0148] index C 0.1C charging capacity 0.1C discharge capacity 1C discharge capacity 3C discharge capacity Compaction -20℃ capacity retention rate 1C room temperature cycle 500 cycles capacity retention rate data 1.63% 110.6mAh / g 99.8mAh / g 87.4mAh / g 78.9mAh / g 2.21g / mL 78.4% 93.2%
Claims
1. A method for preparing a sodium iron sulfate positive electrode material, characterized in that: The method comprises adding a mixture of natrona, sodium sulfate, phosphoric acid and ammonium bicarbonate to a carbon source solution, adjusting the pH of the slurry to 1.8-2.5, and the molar ratio of the added natrona to sodium sulfate, phosphoric acid and carbon source is 1:5.01-5.05:2.01-2.05:0.21-0.
44. After stirring and mixing, grinding, drying and calcining are performed to obtain a sodium ferric sulfate positive electrode material. The method specifically comprises the following steps: 1) Preparation of yellow sodium ferroaluminate: Sodium sulfate, ferric sulfate, titanyl sulfate, urea and pure water are mixed together, heated to 95-105°C under stirring, and reacted at this temperature at a stirring speed of 200-300 r / min for 1-2 hours; then heated to 130-150°C for 1-2 hours, filtered and washed to obtain doped high-crystallinity sodium ferrous ferroaluminate, wherein the molar ratio of sodium sulfate, ferric sulfate, titanyl sulfate and urea is 1.2-1.5:3:0.01-0.03:6.5-7, and the mass of pure water added is 2-3 times the total mass of sodium sulfate, ferric sulfate, titanyl sulfate and urea; 2) adding the obtained mixture of natto alum, sodium sulfate and phosphoric acid to the carbon source solution according to the molar ratio of natto alum to sodium sulfate, phosphoric acid and carbon source of 1:5.01-5.05:2.01-2.05:0.21-0.44, and adjusting the pH of the slurry to 1.8-2.5 with ammonium bicarbonate; 3) After stirring and mixing the slurry in step 2), add it into a ball mill and grind it until the particle size of the slurry is 0.1-0.3 μm; 4) spray drying, the particle size of the spray drying is 10-30 microns, and the moisture content is less than 0.5wt%; 5) The spray-dried material is calcined to obtain the sodium iron sulfate positive electrode material Na 12 Fe6 (SO4)9 (PO4)2.
2. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The calcined material is subjected to air flow pulverization to a particle size of 1.5-2.5 μm, and then sieved, iron removed and vacuum packaged.
3. The method for preparing the sodium iron sulfate positive electrode material according to claim 2, characterized in that: The screening adopts an ultrasonic vibration screen, passes through a 100-mesh screen, and removes iron using an electromagnetic iron remover to remove iron until the content of magnetic foreign matter is less than 1ppm; the vacuum packaging is carried out in a constant temperature and humidity room, the humidity is controlled within 10%, and the temperature is stabilized at 25±5°C.
4. The method for preparing the sodium iron sulfate positive electrode material according to claim 2, characterized in that: The carbon source is a mixture of glucose and pyridine, and the molar ratio of natantium ferroalloy to sodium sulfate, phosphoric acid, glucose and pyridine is 1:5.01-5.05:2.01-2.05:0.2-0.4:0.01-0.
04.
5. The method for preparing the sodium iron sulfate positive electrode material according to claim 2, characterized in that: The mass concentration of the carbon source solution is 1-2%.
6. The method for preparing the sodium iron sulfate positive electrode material according to claim 2, characterized in that: The calcination process has a heating rate of 1.5-2°C / h, followed by a holding stage with a holding temperature of 400-550°C for 6-9h, followed by cooling to a material temperature of ≤100°C at a cooling rate of 1-1.5°C / h.
7. The method for preparing the sodium iron sulfate positive electrode material according to claim 2, characterized in that: During the calcination process, the humidity in the furnace is controlled to be ≤3%, and the calcination is carried out in a nitrogen atmosphere, and the oxygen content in the furnace is less than 5ppm.
Citation Information
Patent Citations
Process for preparing multi-element doped sodium-ion battery electrode materials with jarosite
CN104638260B
A synthetic method of sodium ferric sulfate positive electrode material
CN109192982A
Sodium-ion battery composite positive electrode material and preparation method thereof
CN114267838A
Positive-electrode active material for lithium secondary battery, manufacturing method therefor, positive electrode for lithium secondary battery, and lithium secondary battery provided with said positive electrode
CN104521041A
Process for preparing electrode material of multi-element doped sodium-ion battery by use of sodium jarosite
CN104638260A